2018
DOI: 10.2166/wst.2018.114
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community diversity in a full scale biofilter treating wastewater odor

Abstract: Constantly, the odors coming from sewage plants are considered a problem by the population. The purpose of this study was to evaluate the microbial community present in a full scale biofilter used for odor treatment. The filter was packed with peat. The main gas treated was hydrogen sulphide (HS). The removal efficiency reached 99%, with an empty bed residence time of 30 seconds. Molecular analysis can enhance our understanding of the microbial communities in biofilters treating wastewater odor. The analysis m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Data showed that the predominant phyla in control and treated samples were Proteobacteria, Saccharibacteria and Bacteroidetes. Furthermore, candidate phyla usually found in wastewater, such as WCHB1-60 and TM6 (Tian et al, 2015;Yeoh et al, 2016;Allievi et al, 2018), were also detected in samples. At the genus level, Aquicella, uncultured Saccharibacteria and Flavobacterium dominated the community in both control and treated antibiotic samples ( Fig.…”
Section: Microbial Community Structure and Diversity Of Wastewater MImentioning
confidence: 93%
“…Data showed that the predominant phyla in control and treated samples were Proteobacteria, Saccharibacteria and Bacteroidetes. Furthermore, candidate phyla usually found in wastewater, such as WCHB1-60 and TM6 (Tian et al, 2015;Yeoh et al, 2016;Allievi et al, 2018), were also detected in samples. At the genus level, Aquicella, uncultured Saccharibacteria and Flavobacterium dominated the community in both control and treated antibiotic samples ( Fig.…”
Section: Microbial Community Structure and Diversity Of Wastewater MImentioning
confidence: 93%
“…Correlation analysis of performance and microbes showed that the commonly seen genus Rhodococcus negatively correlated with performance after ozonation. As numerous studies have reported that this genus is dominant in the degradation of xenobiotics in bio lter systems (Portune et al, 2015, Allievi et al, 2018, this indicated a shift in degrading contribution away from Rhodococcus and more toward ASVs from the genera Devosia, Aquamicrobium, and Rhizobiales, which had high positive correlation with performance. The genus Pandoreae was reported to be highly enriched in species capable of effective degradation of xenobiotics (Peeters et al, 2019), and was positively correlated with r>0.7 in both bio lters as shown in Fig.…”
Section: Discussionmentioning
confidence: 81%
“…Mesorhizobium is an genus containing species strongly correlated to nitrogen xation and denitri cation with aerobic respiration, yet the genus was uncommonly reported to be associated with gaseous bio lters, correlation analysis of Mesorhizobium's relative abundance and performance as seen in Fig.5a shows that the genus strongly correlates with mineralization rate of the bio lter after ozonation, this could be explained by enhanced effective use of nitrogen sources through nutrient spraying (Delgado et al, 2007). Proteobacteria in general has been widely reported to contain the dominant degraders of xenobiotics in both bio lter and wastewater treatments (Allievi et al, 2018, Van der Heyden et al, 2019. Proteobacteria has also been reported to have a higher presence in the treatment of more complex pollutants and higher loading stress, inducing higher functional diversity (Friedrich and Lipski 2010).…”
Section: Discussionmentioning
confidence: 99%
“…After ozonation, Proteobacteria increaed in relative abundance, which was widely reported to contain dominant degrader of xenobiotics in both bio lter and wastewater treatments (Allievi, Silveira et al 2018, Van der Heyden, De Mulder et al 2019), reported for higher presence in treatment of more complex pollutant and higher loading stress, inducing higher functional diversity (Friedrich and Lipski 2010). In contrast, this could be a phenotypic embodiment of larger community diversity seen in sequencing results, the ability to better metabolize carbon sources other than the only provided toluene, while degradation of xenobiotics such as toluene had highly diverse prokaryotic pathways, a more even and less specialized phenotypic functional pro le may be desirable in full-scale applications when composition of pollutants is largely uctuated, though this decrease of complex carbohydrate degradation and increases in other compounds caused by ozonation did not impinge removal e ciency of bio lter.…”
Section: Discussionmentioning
confidence: 99%
“…9 out of 20 genera are monotonously correlated with removal e ciency in both ozone and control bio lter, whereas only 3 out of 20 OTUs are monotonously correlated with removal e ciency, indicating a high speci city and different reaction of OTUs under same genus towards ozonation. genus Rhodococcus was reported in numerous studies to be dominant in degrdation of xenobiotics in bio lter systems (Portune, Perez et al 2015, Allievi, Silveira et al 2018, all four OTUs from the genus Rhodococcus present in this system are strongly proportional with removal e ciency in control bio lter but all negatively correlates in ozonated bio lter, suggesting a shift of degrading contribution by Rhodococcus and more towards OTUs of genera Devosia, Aquamicrobium and Rhizobiales with high positive correlation with performance, similar trends of these three genus are seen in combined genus level.…”
Section: Correlation Of System Performance and Dominant Taxamentioning
confidence: 99%